The Role of Medical Students in Patient Safety: A Qualitative Study - Shima Naderi; rouhollah zaboli; Nader Khalesi; Amir Ashkan Nasiripour (Kerman University of Medical Sciences, 2020)
Introduction: Patient safety is one of the main components of health services quality which is defined as the prevention of harm to patients during health care provision. Medical students as members of the treatment team play an important role in patient safety. This study aimed to identify the role of medical students in patient safety in medical centers in Semnan province. Methods: This applied-qualitative study was carried out using a content analysis approach via the framework analysis method. The participants were key informants and experts of patient safety friendly hospital program. They were selected using purposive sampling and the sampling process continued until the data saturation (n=14). The data were collected via semi-structured interviews and analyzed using MAXQDA software (version 10). Results: Of 468 primary codes, 6 main codes were extracted including the importance of student education, student participation in teamwork, interaction with patients, medical errors and patient safety threats, standardization of educational processes, and the importance of completing medical documentation. Conclusion: The results of this study indicated that students have a broad impact on patient safety. Professors and faculty members can improve patient safety and patient satisfaction by interacting with hospital managers, improving the knowledge and clinical capability of medical students, and reducing the impact of negative factors on patient safety.